Estudo da influência de contraíons nas propriedades eletroquímicas, eletromecânicas e térmicas de compósito polímero ionomérico metal (IPMC) de Náfion®/Pt - Tozzi, Kaique Afonso (2022)
In the field of soft actuators, ionomeric polymer metal composite like devices (IPMCs) are a trend, as they display great displacement when a low electric potential is applied. Its work mechanism is related to the migration of solvated counterions inside the polymeric membrane, so the type of counterion plays a key role in the IPMC performance, while keeping the membrane hydrated limits the usage of IPMC's in dry environments. Ionic liquids (ILs) are used in IPMC to solve the dependence of the environment, but with the burden of poor mechanical performance. Thus, the objective of this work was to study the electrochemical, electromechanical and thermal properties of Nafion®/Pt-IPMC with different counterions (H+, Li+, Na+ and [BMIM]+) and to tune the concentration of ionic liquid 1-butyl-3-methylimidazole chloride ([BMIM]Cl) with 0.1; 0.3 or 0.5 mol L-1, attaining electrochemical stability with better electromechanical performance independently of humidity level. [BMIM]Cl was successfully synthesized and characterized through Nuclear Magnetic Resonance, Infrared Spectroscopy with Fourier Transform and Cyclic Voltammetry (CV). IPMC electrochemical behavior was studied through Electrochemical Impedance Spectroscopy, CV and Chronoamperometry, while the electromechanical properties were measured through blocking force and displacement, and mass loss with Thermogravimetric Analysis. IPMC-[BMIM]Cl tests were performed in distinct humidities (30%, 60% and 90%). Concentration of 0.3 mol L-1 provided electrochemical stability with the best electromechanical performance regardless of relative humidity. This result will be important for enhance the devices performance and efficiency.